2006
DOI: 10.1007/s11745-006-5023-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipid class and fatty acid composition of the boreal soft coral Gersemia rubiformis

Abstract: Total lipid, phospholipid, and FA composition and distribution of FA between polar lipids (PL) and neutral lipids (NL) were investigated in the boreal soft coral Gersemia rubiformis from the Bering Sea. The total lipids were mostly hydrocarbons and waxes (33.7%) and PL (33.1%). The content of monoalkyldiacylglycerols (9.7%) exceeded the content of TAG (6.7%). PC and PE constituted 31.4% and 25.6% of total phospholipids, respectively. Principal FA were 16:0, 16:1n-7, 18:0, 18:1n-9, 18:1n-7, 20:1n-7, 20:4n-6, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…It has been reported that total lipid at concentrations of 10–40% of dry biomass was observed in a number of corals from tropical seas [18], [20], [21]. It has also been shown that some coral species maintain enough lipids to sustain their metabolic energy requirements for up to 114 days, when symbiotic algae does not supply the coral with fixed carbon by photosynthetic processes under conditions of insufficient sunlight [25], [26]. Direct observation by light microscopy has revealed that coral eggs contain numerous lipid droplets occupying around 80% of the volume of the egg [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that total lipid at concentrations of 10–40% of dry biomass was observed in a number of corals from tropical seas [18], [20], [21]. It has also been shown that some coral species maintain enough lipids to sustain their metabolic energy requirements for up to 114 days, when symbiotic algae does not supply the coral with fixed carbon by photosynthetic processes under conditions of insufficient sunlight [25], [26]. Direct observation by light microscopy has revealed that coral eggs contain numerous lipid droplets occupying around 80% of the volume of the egg [27].…”
Section: Discussionmentioning
confidence: 99%
“…We suppose that PUFA profiles of the zooxanthellae from soft and reef-building corals are quite similar and some of these acids can be applied as zooxanthellae markers for soft corals. The use of C [20][21][22] PUFA, such as 20:4n-6, 20:5n-3, 22:4n-6, and 22:6n-3, are limited, because high intraspecific variations of the content of these acids exceed interspecific differences [23,24]. In the total FA of corals, octadecapentaenoic acid (18:5n-3) is absent or found only in trace amounts [15,24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, gorgonians survive in conditions where the temperature is between 19°C and 36°C (with a few exceptions). Studies of FA in soft corals have not so far been systematic, and data on the FA contents of total lipids of the corals, especially of gorgonian corals, are limited [17][18][19][20][21][22][23][24]. Only a few works describe the FA of symbiotic dinoflagellates of the reef-building corals [8,11,13,25].…”
Section: Introductionmentioning
confidence: 99%
“…The crustacean Antarctic krill Euphausia superba (Fricke et al, 1986) has been reported to contain 0.3-0.6% DAGE. Recently, the Boreal Soft Coral Gersemia rubiformis (Imbs et al, 2006) has been reported to contain up to 12% DAGE of the total lipids. Hallgren et al (1974a) reported the alkylglycerol content as a percentage of the neutral lipids and phospholipid fractions in the flesh of the teleost fish herring (Clupea harengus) and mackerel (Scomber scomber), in the crustaceans marine crayfish (Nephrops norvegicus), fresh-water crayfish (Astacus fluviatilis) and shrimps (Pandalus borealis), in the molluscs sea mussels (Mytilus edulis) and in cod liver oil.…”
Section: Ocurrence and Distributionmentioning
confidence: 99%